KOMPETENSI PROFESIONAL GURU IPS DI MADRASAH TSANAWIYAH NEGERI BARABAI KABUPATEN HULU SUNGAI TENGAH - Erma Puji Hastuti (JURNAL SOCIUS, 2015)
The purpose of this study is to describe: How mastery of materials, the structure of scientific mastery, mastery of scientific concepts and mastery mindset social studies teacher at MTsN Barabai. The method used in this research is descriptive qualitative method. Where the data collected by observing, interview and documentation. The results showed that the Master IPS in MTsN Barabai Hulu Sungai Tengah has the ability in mastering the learning material, master the structure of science, master the concepts of science and master of science supporting mindset subjects diampunya.Keywords: professional competence of teachers, and social studies